How farm practices and antibiotic use drive disease incidence in smallholder livestock farms: Evidence from a survey in Uganda - Emes, E.; Wieland, Barbara; Magnusson, Ulf; Dione, Michel M. (Elsevier, 2023)
Background Antimicrobial resistance (AMR) is a growing threat to human and animal health, and the growth in AMR prevalence globally is thought to be partially driven by non-therapeutic antibiotic use in livestock production. However, livestock farms may depend on antibiotics as a prophylactic disease management tool, and reducing antibiotic use in isolation may harm farmers' economic security. In order to help farmers safely reduce their antibiotic use, we must first determine how necessary non-therapeutic antibiotic use is for disease management, and how other farm practices can guard against disease and make antibiotic use reduction safe and feasible.